Manifestări ale autismului naţionalofob în presa postdecembristă: de la „identităţile interşanjabile” la „negustorii de iluzii” - Nicoleta Ifrim (Revista de Istorie și Teorie Literară)
Within the post-December period, the Romanian cultural background has witnessed the conflictive phenomenon of critical revision focusing on the (in)validation of the literary canon by means of two dichotomic approaches: the ethicist one looking for the ‘moral guilt’ of both the writer and his writing (the collaborationist syndrome) and the aesthetic perspective analysing the inner fictional mechanism and strategies conveying the value of the literary work. A new prototype of criticism has occurred: the ‘national-phobic’ autism that aims at demolishing the ‘aesthetically-oriented literary canon’ in favour of the ‘democratic’ one, which would preserve the ‘non-collaborationist’ drive.